2016
DOI: 10.1007/s13197-016-2425-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of vacuum packaging and mint extract treatment on the biochemical, sensory and microbial changes of chill stored Indian mackerel

Abstract: The present study was aimed to investigate the combined effects of vacuum packaging and mint extract treatment on the quality changes of gutted Indian mackerel (Rastrelliger kanagurta) during storage at 0-2°C for 22 days. Biochemical, total viable count and sensory quality of chill stored mackerel were analysed at periodic intervals. Mint extract treated [dipping in 0.5% (w/v) solution of mint extract for 30 min] and vacuum packed fishes (MEVP) had significantly lower total volatile base nitrogen and trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(53 reference statements)
2
9
1
Order By: Relevance
“…The increasing demand for fresh chilled fish with an extended shelf life has intensified the search of technologies that support fresh fish quality. One of the main developments is the modification of the atmosphere packaging (Viji et al, 2016), or the use of edible coatings (Fan et al, 2009;Jian, Wenyi, & Wuyong, 2011) and active bio-based packaging (Heydari, Alemzadeh, & Vossoughi, 2013). Gelatin edible coating can act as a barrier to the permeability of oxygen and, thereby it can reduce the oxidation reactions and food products deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing demand for fresh chilled fish with an extended shelf life has intensified the search of technologies that support fresh fish quality. One of the main developments is the modification of the atmosphere packaging (Viji et al, 2016), or the use of edible coatings (Fan et al, 2009;Jian, Wenyi, & Wuyong, 2011) and active bio-based packaging (Heydari, Alemzadeh, & Vossoughi, 2013). Gelatin edible coating can act as a barrier to the permeability of oxygen and, thereby it can reduce the oxidation reactions and food products deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Viji et al. (2016) and Castada et al. (2017) reported that RA was effective at removing the disagreeable odors of garlic and mackerel.…”
Section: Resultsmentioning
confidence: 90%
“…Different results have been reported in various studies for fresh mackerel in terms of lipid oxidation parameters [ 29 ]. This could be attributed to the impacts of the catching period and feeding habit, causing variation in total lipid content [ 30 ] and impacts of processing conditions.…”
Section: Resultsmentioning
confidence: 99%